Simultaneous leadless pacemaker and subcutaneous implantable cardioverter‐defibrillator implantation—When vascular options have run out. Issue 1 (20th November 2018) - Ng, Jit Beng; Chua, Kelvin; Teo, Wee Siong
Abstract: An end‐stage renal failure patient who was planned for a left brachioaxillary arteriovenous graft required an implantable cardioverter‐defibrillator for secondary prevention of ventricular tachycardia and a pacemaker for complete heart block but was found to have a right subclavian venous occlusion. Due to the lack of vascular access, we performed a successful subcutaneous implantable cardioverter‐defibrillator (S‐ICD) and leadless pacemaker implantation. There was no interaction between the devices at the time of implantation, during defibrillation testing and following an appropriate defibrillation therapy.